2017
DOI: 10.1136/jim-2016-000270
|View full text |Cite
|
Sign up to set email alerts
|

Proposal of a Dukes-Mac-Like Staging System for Gastric Cancer

Abstract: The aim of this study was to present an epidemiological update regarding the classical prognostic parameters of gastric cancer (GC) in 3 countries from Eastern Europe and to suggest a modification of the pTNM staging system. In 333 consecutive cases which were diagnosed between 2003 and 2012 in 3 departments of pathology from Romania, Hungary, and Poland, the following parameters were analyzed: age and gender of patients, tumor localization, macroscopic and microscopic aspects including the degree of discohesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…As overall survival varies in patients with GC within the same stage, the most recent papers have shown that the currently used TNM staging system is not sufficient for prognosis estimation[ 1 ]. The present study confirmed the utility of the newest Dukes-MAC-like staging system[ 9 ], for a proper estimation of long-time survival, and confirmed the independent prognostic role of IHC expression of Maspin and p53, in patients with GC. Despite the intention of including new biomarkers with prognostic potential, the depth of invasion, combined with lymph node status (pTN stage) remain the strongest predictors of outcome in patients with GC[ 8 , 11 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As overall survival varies in patients with GC within the same stage, the most recent papers have shown that the currently used TNM staging system is not sufficient for prognosis estimation[ 1 ]. The present study confirmed the utility of the newest Dukes-MAC-like staging system[ 9 ], for a proper estimation of long-time survival, and confirmed the independent prognostic role of IHC expression of Maspin and p53, in patients with GC. Despite the intention of including new biomarkers with prognostic potential, the depth of invasion, combined with lymph node status (pTN stage) remain the strongest predictors of outcome in patients with GC[ 8 , 11 ].…”
Section: Discussionsupporting
confidence: 85%
“…The second system used for tumor staging was proposed by our team in 2017 and is called the Dukes-MAC-like staging system[ 9 ]. This system consists of the classification of GCs, based on the depth of invasion (T) and lymph node status (N), in eight groups, as follows: 1-T1N0; 2-T1N1-3; 3-T2N0; 4-T2N1-3; 5-T3N0; 6-T3N1-3; 7-T4N0; 8-T4N1-3[ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…[ 3 , 16 , 17 ] In addition, LNR was first carried out by Nitti D, et al as a significant independent prognostic factor in gastric cancer. [ 18 ] Except pN and LNR, LODDS as the log of the ratio between the number of positive and negative lymph nodes [ 19 ] and Dukes-MAC-like pTN staging system [ 20 ] were also shown as strong prognostic indicators in gastric cancer. However, many outcomes of latest researches have confirmed LNR's value and considered it could be better than other lymph node related parameters to predict prognosis because it is less affected by the the extent of lymphadenectomy and the accuracy of positive lymph nodes number detected by pathologists.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to establish the staging according to the most recent edition of the American Joint Committee on Cancer tumor staging manual [ 11 ]. Tumors were also staged according to the Dukes-MAC-like staging system, proposed in 2017 [ 12 ].…”
Section: Methodsmentioning
confidence: 99%